Nursing Care for Children with Cyanotic Heart Disease at Risk of Cyanotic Spells - Theannamngian, Onchira (Thai Red Cross Nursing Journal, 2023)
Cyanotic spells are the greatest complication in pediatric patients with congenital cyanosis, who have little blood in their lungs while waiting for surgery to correct the abnormality. As a result, the brain lacks oxygen, leading to seizures and possibly even death. Therefore, the condition is a medical emergency that requires timely assistance. The purpose of this article is to enable nurses to accurately provide care for patients at risk of developing cyanotic spells and to advise parents on how to care for their children while at home. The study presents the causes and mechanisms of the occurrence, the causal factors promoting the condition, its signs and symptoms, treatment, nursing of the patient when cyanotic spells occur, preventing, and important advice for parents caring for patients at home. Understanding cyanotic spells will help nurses assess symptoms and provide timely support to patients, as well as develop a nursing plan to keep these patients safe from cyanotic spells both in the hospital and at home. The study also provides advice for parents on how to properly care for their children, which will help patients receive continuous care and remain safe from cyanotic spells until surgery is performed, which will affect the patient’s quality of life.